PENGARUH VARIASI CAMPURAN BAHAN BAKAR SOLAR DAN MINYAK KELAPA SAWIT TERHADAP PUTARAN MOTOR DIESEL TIPE RINO 115PS - VINA N VAN HARLING (SOSCIED, 2019)
This research was conducted to determine the effect of variations in the mixture of diesel fuel and palm oil on the 115PS Rino Type Diesel motor rotation. The study was conducted with a variety of pure diesel fuel, a mixture of diesel 70% palm oil 30%, diesel 50% palm oil 50%, and diesel mix 30% palm oil 70%. Based on the results of tests conducted obtained greater engine speed (rpm) data generated by the use of pure diesel fuel with a 7 mm gas screw adjustment of 1800 rpm. Whereas the lower engine speed (rpm) results from the use of a 30% diesel fuel mixture with 70% palm oil with a 2 mm gas screw adjustment of 620 rpm